The dynamic stock returns volatility and macroeconomic factors in Malaysia: A sectoral study - Saizal Pinjaman; Sarma Aralas (Zes Rokman Resources, 2015)
This paper analyzes the impact of selected macroeconomic factors, namely Gross Domestic Product, exchange rate, interest rate, inflation rate, money supply, economic crisis and economic liberalization towards stock returns volatility of four economic sectors in Malaysia. In this paper, the dynamic stock returns volatility estimation shows that stock returns volatility is persistent in nature where previous shock will influence the current stock performance. This research also documents the existence of leverage effects in the stock market, where negative news brings larger magnitude of shocks compared to positive news. Based on cross-sectional time series model, the investigation shows significant relationships of all macroeconomic factors towards stock returns volatility across all economic sectors. This paper is important for policy makers, firms and academicians.